2001
DOI: 10.1177/01939450122045339
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognitive Factors Predicting the Health of Elders

Abstract: The social cognitive model of health is primarily concerned with influences on a person's decisions to perform health behaviors. In this study, the relationships among social cognitive factors reflecting enabling skills (learned resourcefulness), internal motivation for health (health self-determinism), and help responses (coping responses) and a measure of physical and psychosocial health were examined in 137 chronically ill elders. Gender, race, and number of chronic conditions were predictors of learned res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Similarly, Zauszniewski (1996) found a significant relationship between depressive cognitions and lower personal and social resourcefulness in healthy, community dwelling elders, while greater personal resourcefulness was associated with the absence of depressive cognitions and with more adaptive functioning. Research has shown that resourcefulness leads to adaptive functioning in depressed adults (Zauszniewski, 1995(Zauszniewski, , 1996, life satisfaction in persons with chronic pain and healthy elders (Lefort, Gray-Donald, Rowart, & Jeans, 1998), and better perceived health in caregivers and in diabetic women (Rapp et al, 1998;Zauszniewski et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Zauszniewski (1996) found a significant relationship between depressive cognitions and lower personal and social resourcefulness in healthy, community dwelling elders, while greater personal resourcefulness was associated with the absence of depressive cognitions and with more adaptive functioning. Research has shown that resourcefulness leads to adaptive functioning in depressed adults (Zauszniewski, 1995(Zauszniewski, , 1996, life satisfaction in persons with chronic pain and healthy elders (Lefort, Gray-Donald, Rowart, & Jeans, 1998), and better perceived health in caregivers and in diabetic women (Rapp et al, 1998;Zauszniewski et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Studies also have shown that persons with greater resourcefulness report more positive affect, fewer depressive cognitions (Zauszniewski, Bekhet, Lai, McDonald, & Musil, 2007), and better self-rated health and functioning (Zauszniewski, Eggenschwiler, Preechawong, Roberts, & Morris, 2006). In addition, greater resourcefulness has been found to predict better self-care (Kreulen & Braden, 2004) and psychological and physical health (Zauszniewski et al, 2001) and to influence positive behavior change (Lévesque, Gauvin, & Desharnais, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among those serving as caregivers to older adults, resourcefulness is related to better task performance, adaptive and social-role functioning, health behaviors, psychological well-being (Fingerman, Gallagher-Thompson, Lovett, & Rose, 1996; Gonzalez, 1997; Picot, Zauszniewski, & Delgado, 1997; Rapp, Schumaker, Schmidt, Naughton, & Anderson, 1998; Zauszniewski, 1996; Zauszniewski & Chung, 2001; Zauszniewski, Chung, & Krafcik, 2001) and to less caregiver burden (Intrieri & Rapp, 1994; Zauszniewski, 1997). Although grandmothers raising grandchildren report more depressive symptoms, they show no differences in resourcefulness (Musil et al, 2009) when compared with grandmothers living in multigenerational homes or who are non-caregivers to grandchildren.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, improved understanding of patients' perceptions of and views regarding their illness may benefit patient care as these perceptions can influence the ways in which individuals cope with and adapt to their illness (Caress, Luker, & Owens, 2008;Nannis, Patterson, & Semple, 1997). For example, health care providers might enhance coping strategies in older women by teaching them ways to reframe how they view unchangeable conditions and incorporate strategies to increase elders' comfort with chronic conditions (Martin, 2003;Zauszniewski, Chung, & Krafcik, 2001).…”
Section: Discussionmentioning
confidence: 99%